2009
DOI: 10.2495/cmem090451
|View full text |Cite
|
Sign up to set email alerts
|

Growth behavior of small surface cracks in coarse and ultrafine grained copper

Abstract: Since fatigue life of a plain specimen of ductile metals is controlled mainly by the propagation life of a small surface crack, to clarify the growth behavior of a small crack is crucial to the safe design of smooth members. However, little has been reported on the growth behavior of small surface cracks in ultrafine grained (UFG) metals. In the present study, stress-controlled fatigue tests for coarse grained (CG) and UFG copper were conducted. The surface damage evolution during cyclic stressing was observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Accordingly, the shorter fatigue life of UFG12 at medium and low stress amplitudes resulted from diminished crack initiation life because of accelerated slip band formation caused by early formation of large recrystallized grains. It has been shown that the difference in pass number in UFG copper has a negligible effect on the crack growth rate [15]. Here, one should be aware that the occurrence of the dynamically recovered grains in UFG4 never imply no generation of dynamically recrystallized grains.…”
Section: Resultsmentioning
confidence: 90%
“…Accordingly, the shorter fatigue life of UFG12 at medium and low stress amplitudes resulted from diminished crack initiation life because of accelerated slip band formation caused by early formation of large recrystallized grains. It has been shown that the difference in pass number in UFG copper has a negligible effect on the crack growth rate [15]. Here, one should be aware that the occurrence of the dynamically recovered grains in UFG4 never imply no generation of dynamically recrystallized grains.…”
Section: Resultsmentioning
confidence: 90%
“…(2) for determining the growth rate of small cracks at high stress amplitudes: (2) where D and n are material constants. The growth data of small cracks in various metals indicated that dl/dN of a mechanically small crack is uniquely determined by the term  a n l and not by ΔK [6,9,10]. Fig.…”
Section: Figure 11mentioning
confidence: 99%